Taxation and Public Health Regulation in Nigeria: Prospects and Challenges - Ajagunna, Folakemi O. (ABUAD Law Journal, 2021)
Unhealthy behaviours such as smoking, drinking excess alcohol and unhealthy diets have been identified as key drivers of poor health outcomes and have significant consequences for individuals. One of the core duties of the state via the instrument of public health law is to ensure that individuals stay healthy through maintaining healthy lifestyle choices. In most instances, this is not really the case as individuals engage in activities that are detrimental to their health. Whilst individuals have rights to privacy and freedom of choices, nevertheless the state has an inherent duty under the Constitution to ensure the populace stays healthy. This paper examines the prospects and challenges of regulating unhealthy behaviours through taxation. It adopts a desk-based method to examine the prospects and challenges associated with health taxes. It cautions against having economic motives alone for imposing health taxes and recommends that other approaches like increasing awareness about unhealthy habits should be embraced alongside health taxes. The paper concludes that health taxes are relevant to curb increasing disease burden in Nigeria.